Desenvolvimento e caracterização de sistemas multiparticualdos de liberação prolongada para o antiinflamatório cetoprofeno - OLIVEIRA, Rodinelli Borges de (2010)
Ketoprofen is a nonsteroid anti-inflammatory drug (NSAID) which is used in rheumatic disorders and in mild to moderate pain. Ketoprofen has a short biological half life and the commercially available conventional release formulations require dosages to be administered at least 2-3 times a day. Due to these characteristics, ketoprofen is a good candidate for the preparation of controlled release formulations. In this work, a multiparticulate sustained release dosage form containing ketoprofen in a carnauba wax matrix was developed. Particles were prepared by emulsion congealing technique, spray drying, fluidized bed and conventional granulation. Hydroxypropylmethylcellulose (HPMC) and carnauba wax were used in the formulations as the main ingredients to promote sustained release. Particles were evaluated for their rheological properties, morphology and drug release characteristics. For the emulsion congealing technique, system variables were optimized using fractional factorial and response surface experimental design in order to obtain spherical particles with high drug load and sustained drug release profile. The optimized particles had an average diameter of approximately 200 μm, 50% (w/w) drug load, good flow properties and a prolonged release profile (up to 24 hours) for ketoprofen. Particles prepared with HPMC 2208 by spray drying, fluidized bed and conventional granulation did not exhibit prolonged release of the ketoprofen after the dispersion of the drug dosage for in the dissolution medium. Due to their good flowability and capability in prolonging ketoprofen release, carnauba wax pellets prepared by emulsion congealing were submitted to permeation studies through Wistar rats intestinal segments. Results demonstrated that carnauba wax microparticles were able to promote continuous and sustained ketoprofen release, leading to high apparent permeability coefficient in the upper small intestine. Carnauba wax microspheres prepared in this work represent a new multiparticulate sustained release system for the NSAID ketoprofen, exhibiting good potential for application in further pharmaceutical processes. In addition, the microspheres can be prepared without incorporating the drug and used as an excipient in direct compression processes.